Knee joint extension limitation in female patients with knee osteoarthritis affects the infrapatellar fat pad hardness and hemoglobin concentration by isometric quadriceps exercise - Syoya Nakanishi; Masahiro Tsutsumi; Takashi Kitagawa; Toshinori Miyashita; Makoto Wada; Shintarou Kudo (Osteoarthritis and Cartilage Open)
Objective: To investigate whether there is a difference in hardness and hemoglobin concentration changes in the infrapatellar fat pad (IFP) during isometric quadriceps exercise (IQE) in patients with knee osteoarthritis (KOA) between those with and without knee extension limitation. Design: In this cross-sectional study, data were collected at an orthopedic clinic from March 2022 to April 2023. Among patients diagnosed with KOA, those with knee joint extension range of motion <0° and >0° were defined as the limited group (n ​= ​16) and non-limited group (n ​= ​13), respectively. Ultrasonography was performed at rest and during IQE to measure IFP hardness based on shear wave velocity. Near-infrared spectroscopy was performed to measure oxygenated hemoglobin (O2Hb), deoxygenated hemoglobin (HHb), and total hemoglobin (cHb) in the IFP before (baseline), during (IQE task), and post IQE. IFP hardness and O2Hb, HHb, and cHb concentration were analyzed using a linear mixed model for the groups and measurement points. Results: IFP hardness changes during IQE were significantly less in the limited group than in the non-limited group (limited: mean difference [MD] ​= ​−0.136, 95 ​% confidence interval [CI] [−0.475, 0.203]; non-limited: MD ​= ​−1.154, 95 ​% CI [−1.530, −0.778]). O2Hb concentration did not significantly change at post compared with baseline in the limited group but did in the non-limited group (limited: MD ​= ​−0.024, 95 ​% CI [−0.961, 0.913]; non-limited: MD ​= ​−4.118, 95 ​% CI [−5.156, −3.079]). Conclusions: The limited group revealed no IFP hardness and hemoglobin concentration change following IQE, whereas the opposite was observed for the non-limited group, indicating oxygenation.